Enhydra XMLC™ Java™ Presentation Development - Young, David (Sams, 2002)
Enhydra XMLC Java Presentation Development is written for computer professionals, with a special focus on application architects, Java Web application developers, and those who are just ramping up on Java and are excited about immersing themselves into Web application development. Taking a task view wherever possible, this book is written to support those seeking a more elegant, maintainable, and flexible mechanism for building Web application presentations. While we spend some time introducing the Enhydra application server for those who are new to the topic of application server development, this book is focused primarily on the topic of Enhydra XMLC and how to use it to improve the lifecycle requirements of your Web application.
Includes bibliographical references and index
Keywords: Java (Computer program language); Object-oriented programming languages; Java (Langage de programmation); Langages orientés objet (Informatique); COMPUTERS; Data Processing; Engineering & Applied Sciences; Computer Science; Instructional and educational works; Matériel d'éducation et de formation